The Archetype of Maleficent In Maleficent Movie By Robert Stromberg - , FAJARBAGUSDWIYONO (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2019)
Maleficent is an American dark fantasy film produced by Robert Stormberg in 2014, from a screenplay by Linda Wooverton. This movie is an adaptation of Walt Disney’s Sleeping Beauty (1959). The point of this thesis was to reveal the character of Maleficent herself as by standart in fairy tales she had multiple character inside of her. For some reason she is the witch, but for some people she is the fairy godmother. The binary opposition here is loud and clear so it is hard to distinguish the character inside Maleficent herself, thus the theory of Archetype by Carl Gustav Jung were used to differentiate what is Maleficent in this story, what role is being taken as her purpose, what are the definitive changes through the movie that Maleficent undergoes. All of the question were thrown into two main research which are the type of archetype in Maleficent and the individuation process of Maleficent. First topic of analysis will be the four main archetype of carl gustav jung that can be extracted from a literal 300 type of archetypes in literature section. The four main archetype is the persona which means the mask of a person, the shadow which an evli lurks beneath the character, anima and animus which about the binary consciousness of one’s character depends on the gender, and lastly the self, which happens to be the final archetype that combined from the ID and the ego of one’s character. Second analysis will be the individuation process of the character throughout the movie. Maleficent as a witch, originally, is not a merely simple witch just like how the fairy tales go, rather that she is a complex character that experience a development.